Pharmaceuticals active compounds in the aquatic environment: a review - Yashni, G.; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Mohd Salleh, Siti Nor Aishah (Penerbit UTHM, 2020)
Pharmaceutical active substances utilised to treat human and animal diseases can launch into the environment through effluents from wastewater treatment plants and direct disposal of pharmaceutical compounds. Some of these compounds arrive in the environment as a parent compound or as active/inactive metabolites. Owing to their pharmacological action, their conceptions in the environment are significant, and thus this chapter reviews the understanding of the presence of pharmaceutical compounds in the environment.